Project “Equalizing opportunities – raising competence of children with disabilities” - Piasecki, Bartosz; Mojs, Ewa; Sudoł, Anna; Samborski, Włodzimierz (Journal of Medical Science, 2015)
The project will enable the use of the Tomatis therapy for children with central auditory processing disorders and the introduction of a proprietary curriculum preparing children to learn English in primary school – based on the method that streamlines the auditory analysis, on the proprietary language integration CDs used in the Tomatis method and on individual educational and therapeutic lessons with the teacher. The curriculum will be developed in the course of research under the guidance of prof. UM dr hab. Ewa Mojs from the Poznan University of Medical Sciences. The leader of the consortium implementing the project is the Foundation for Local Activity. The innovation has a high potential for implementation. Applicants to begin with estimate ultimately the ability to implement the program in the first year in 350 schools with the right equipment.
Keywords: Tomatis therapy for children; primary school